2009
DOI: 10.1242/dmm.002527
|View full text |Cite
|
Sign up to set email alerts
|

An ENU-induced mutation in mouse glycyl-tRNA synthetase (GARS) causes peripheral sensory and motor phenotypes creating a model of Charcot-Marie-Tooth type 2D peripheral neuropathy

Abstract: C201R, with a point mutation that leads to a non-conservative substitution within GARS. Heterozygous mice with a C3H genetic background have loss of grip strength, decreased motor flexibility and disruption of fine motor control; this relatively mild phenotype is more severe on a C57BL/6 background. Homozygous mutants have a highly deleterious set of features, including movement difficulties and death before weaning. Heterozygous animals have a reduction in axon diameter in peripheral nerves, slowing of nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
167
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(185 citation statements)
references
References 43 publications
10
167
2
Order By: Relevance
“…The greatest sensory deficiency in patients with CMT2D is in the perception of vibration, which is sensed by neurons with large cell bodies and axons (26,27); however, patient sural nerve biopsies show a selective loss of small sensory axons (20,21). This histological finding is also counter to what is observed in CMT2D mice; the milder Gars C201R/+ mice display a general reduction in axon diameter in both the saphenous and sensory femoral nerves (12), whereas the more severe Gars Nmf249/+ allele displays both a reduction in axon diameter and axon number (11); nevertheless, whether specific sensory neuron populations are preferentially atrophied or lost is unknown. We thus set out to interrogate the sensory nervous system of CMT2D mice to better understand how and when Gars mutations cause sensory pathology, its molecular mechanism, and the effect that these mutations have on sensation of the external environment.…”
Section: Significancementioning
confidence: 86%
See 4 more Smart Citations
“…The greatest sensory deficiency in patients with CMT2D is in the perception of vibration, which is sensed by neurons with large cell bodies and axons (26,27); however, patient sural nerve biopsies show a selective loss of small sensory axons (20,21). This histological finding is also counter to what is observed in CMT2D mice; the milder Gars C201R/+ mice display a general reduction in axon diameter in both the saphenous and sensory femoral nerves (12), whereas the more severe Gars Nmf249/+ allele displays both a reduction in axon diameter and axon number (11); nevertheless, whether specific sensory neuron populations are preferentially atrophied or lost is unknown. We thus set out to interrogate the sensory nervous system of CMT2D mice to better understand how and when Gars mutations cause sensory pathology, its molecular mechanism, and the effect that these mutations have on sensation of the external environment.…”
Section: Significancementioning
confidence: 86%
“…A previous study has shown that expression of TrkC from the TrkA locus caused a developmental fate switch in DRG sensory subtypes (63). Given that GlyRS is expressed during early development (11,12), and that arborization of nociceptive neurons is developmentally impaired in CMT2D mice (Fig. 5F), our work has identified a highly plausible mechanism to account for the sensory neuron identity defects observed in Gars animals; namely, mutant GlyRS binds and spuriously activates multiple Trk receptors, thereby subtly subverting sensory neuron differentiation and/or survival during early stages of development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations